Immunological Detection of Newcastle Disease Viral Antigen in the Naturally Infected Chickens by Monoclonal Antibodies against Fusion-2 Protein - Astawa, Nyoman Mantik; Mirah Adi, Anak Agung Ayu (Jurnal Veteriner; Vol 15 No 2 (2014), 2014)
Monoclonal antibodies (mAbs) against Fusion (F)2 protein of Newcastle disease virus (NDV) wereproduced for the detection of the viral antigen in infected chickens. Cells derived from spleen of Balb/c miceimmunized with the virus were fused with mouse myeloma cells to generate hybridomas capable ofproducing mAbs against the virus. The hybridomas were screened by enzyme-linked immunosorbent assay(ELISA) for anti-NDV specific mAbs using crude viral antigen (allantoic fluid of NDV-infected fertile eggs)and normal uninfected allantoic fluid of fertile eggs as negative control. The NDV proteins reactive withmAbs were then determined by Western Blotting using purified NDV as antigen. The mAbs reactive withF2 (12.5 KDa) protein of NDV were then used for the detection of NDV antigen in both the allantoic fluidof NDV- infected chicken embryos and in organs of naturally infected chickens. The results showed that 2out of 5 mAbs produced were against F2 protein of NDV. By indirect ELISA, the mAbs were able to detectthe viral antigen in allantoic fluid of NDV infected fertile chicken eggs at the titre as low as 2-2 to 2-4 HAunits per 0.1 mL. NDV–antigen was also detected by immunoperoxidase staining in paraffin-embeddedtissues of NDV-infected chickens but not in normal uninfected chickens. The most prominent infection wasdetected in the gastrointestinal tract and the lung. The NDV antigen was also detected in other organssuch as the brain, spleen, and several other tissues. It is evident that mAbs produced against F2 proteinof NDV were applicable for use in the detection of NDV antigen in infected chickens.
Keywords: Newcastle, virus, monoclonal antibodies